Characterization of the components of the thioredoxin system in Bacteroides fragilis and evaluation of its activity during oxidative stress. (February 2022) - Paunkov, Ana; Kupc, Małgorzata; Sóki, József; Leitsch, David
Abstract: Objectives: Bacteroides fragilis has a pronounced ability to survive prolonged exposure to atmospheric oxygen. The major objective of this study was to biochemically characterize the components of the thioredoxin system in B. fragilis . The nitroreductase activity of TrxR was also assayed. Methods: Components of the thioredoxin system were expressed in E. coli and used in a disulfide reductase activity assay. Activity of TrxR was measured with purified recombinant enzyme or with cell extracts after or without exposure to oxygen or hydrogen peroxide, respectively. Results: Of all six thioredoxins tested, only thioredoxins A, D, and F were reduced by recombinant TrxR and natural TrxR present in B . fragilis cell extracts. Exposure to oxygen and hydrogen peroxide increased the activity of TrxR. Further, B . fragilis TrxR acts as a nitroreductase with furazolidone or 1-Chloro-2, 4-dinitrobenzene as substrates but cannot reduce metronidazole. Conclusion: TrxR shows an increase in activity under the conditions of oxidative stress and exerts nitroreductase activity. Highlights: Recombinant thioredoxin reductase (TrxR) reduces thioredoxins A, D and F. Thioredoxins A, D and F in cell extracts are reduced by recombinant TrxR. Exposure of cells to O2 or H2 O2 increases activity of TrxR. Recombinant TrxR reduces furazolidone and CDNB but not metronidazole.